Relação de atributos do solo sobre a densidade populacional de fitonematoides e o estado nutricional do algodoeiro na produção e qualidade da fibra - Silveira, Omar Roberto da (2021)
Cotton crop is very important for the Brazilian economy, but it has suffered considerable losses in fiber yield and quality caused by plant-parasitic nematodes. Researches concluded that some soil physical and chemical attributes change the population density of certain nematodes. However, the management of soil physical and chemical attributes levels for nematode control by cotton growers depends on study that relates cotton-parasitic nematodes to soil physical and chemical attributes, which can be managed through agricultural practices. Study should be carried out in regions and conditions of cotton growing and also determining the nematodes effects on cotton nutrients levels, as well as the soil chemical attributes levels on cotton fiber production and quality. Thus, we studied the relations between 8 soil physical attributes, 28 soil chemical attributes, 13 foliar nutrients, cotton fiber yield, ginning out turn, 10 fiber quality attributes, population density of the nematodes Pratylenchus brachyurus (Pb), Rotylenchulus reniformis (Rr), Meloidogyne incognita (Mi), and Helicotylenchus dihystera (Hd) besides their eggs number in the soil and cotton root. We sampled 200 points from 100 cotton fields, involving 13 cotton cultivars, between 63 and 136 days after cotton emergence, distributed throughout in the counties of Nova Mutum, Pedra Preta, and Campo Verde, Mato Grosso State, Brazil, at altitudes from 402 to 885 m. We also sampled 20 soil trench, each one 0.5 m deep with 5 layers at 1 field of cotton growing, in a latosol in the county of Nova Mutum, Mato Grosso State, Brazil. The sample data were submitted to (i) Canonical Correspondence Analysis (CCA) and Principal Component Analysis (PCA), which explained from 60.71 to 99.83 % of the sample data variability, (ii) Non-metric Multidimensional Scaling Analysis (nMDS) that explained the total variance of the sample data with 0.1382 ≤ Stress ≤ 0.1578 and also 0.79 ≤ R2 ≤ 0.86, (iii) Analysis of Similarity (ANOSIM) and Similarity Percentage Analysis (SIMPER). The results showed mainly being (Ntotal=total nitrogen, CTC=cation exchange capacity): (i) silt and microporosity levels afect the number of phytonematode eggs and the nematode population density; (ii) nematodes can associate to the soil color; (iii) soil physical attributes levels influenced Pb population density in cotton root; (iv) K and Ntotal in soil, as well as Mg, H+Al, and K/CTC in cotton root varied the number of phytonematode eggs and the nematode population density; (v) soil chemical attributes differentiated the Mi population density in solo besides Pb and Hd population density in cotton root; (vi) in cotton root Pb and Hd from one side, as well as Mi and Rr from the other side reduced and elevated foliar nutrient levels, respectively; (vii) B, Zn, Mo, Mn, and Ni foliar changed the cotton yield, ginning out turn, and fiber yield; (viii) P, Ni, and Fe foliar modified the cotton fiber quality; (ix) cotton root contained the largest population density of Pb and soil hosted more Rr and Hd; (x) soil physical and chemical attributes affected nematode distribution in the 0.5 m depth layer; (xi) Rr showed more competitive than the other nematodes. We concluded as follows: (i) elevation or reduction of soil physical and chemical attributes levels can diminish the number of phytonematode eggs and the nematode population density of Mi, Pb, Rr, and Hd that are present in the soil and in cotton root; (ii) Mi and Rr associate to the soil color, but it does not occur with Pb and Hd; (iii) Mi, Pb, Rr, and Hd in cotton root change foliar nutrient levels; (iv) elevation or reduction of foliar nutrient levels can increase the cotton yield, ginning out turn, and fiber yield, as well as it can improve the cotton fiber quality; (v) soil physical and chemical attributes affect the distribution of Mi, Pb, Rr, and Hd in the 0.5 m depth layer; (vi) Rr is more competitive than Hd, Pb, and Mi in the soil, as well as in cotton root; (vii) Rr inhabits the 0-0.5 m depth layer in the same proportion; (viii) macroporosity prevents cotton root deepening in the 0.1-0.2 m deep layer due to soil aeration deficiency, whereas soil chemical attributes do it from 0.2 up to 0.5 m deep layers because of fertility insufficiency; (ix) soil bulk density is not appropriate to evaluate cotton root growing in Latosol being preferable macroporosity and microporosity.